THE EFFECT OF SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) TEACHING METHOD AND READING INTEREST TOWARD READING COMPREHENSIONS OF CHILDREN STORIES ABILITY (EXPERIMEN RESEARCH IN THE 5th GRADE OF ELEMENTARY SCHOOL AT LAWEYAN DISTRICTS SURAKARTA - Miftakhul Husna; St. Y. Slamet; Jenny Indrastoeti Siti Poerwanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research 1) The difference of reading  comprehensions of children stories ability that taught by SQ3R teaching method within CIRC teaching method, 2) The difference of reading comprehensions of children stories ability between students who had high interest in reading and students who had low interest in reading, 3) The interaction between teaching method and reading interes. This research used quasi experimental  method with randomized contract group pretest-postest used factorial 2x2 design. The result of this research showed that: 1) There was the difference of reading  comprehensions of children stories ability that teach  SQ3R teaching method and students who were taught by CIRC teaching method 2 ) there was the difference of between students who had high interest in reading and students who had low interest in reading 3) There was interaction between teaching method and reading interest